Diagnosis and Management of Melanoma of the Scalp: A Review of the Literature - Licata G; Scharf C; Ronchi A; Pellerone S; Argenziano G; Verolino P; Moscarella E (Dove Medical Press, 2021)
Gaetano Licata,1 Camila Scharf,1 Andrea Ronchi,2 Sebastiano Pellerone,1 Giuseppe Argenziano,1 Pasquale Verolino,3 Elvira Moscarella1 1Dermatology Unit, Department of Mental and Physical Health and Preventive Medicine, University of Campania Luigi Vanvitelli Naples, Naples, Italy; 2Pathology Unit, Department of Mental and Physical Health and Preventive Medicine, University of Campania Luigi Vanvitelli Naples, Naples, Italy; 3Plastic Surgery Unit, Multidisciplinary Department of Medical-Surgical and Dental Specialties, University of Campania Luigi Vanvitelli Naples, Naples, ItalyCorrespondence: Giuseppe Argenziano Email g.argenziano@gmail.comAbstract: Cutaneous melanoma is a public health issue and the head and neck region is of particular interest, despite accounting for only 9.0% of the total body surface, it harbours 20% of melanoma cases. Data from the literature show that scalp melanomas (SM) carry high mortality rates, with a 10-year survival rate of 60% which lead them to be named as the "invisible killer". Moreover, SMs are more common in the elderly than in young population, and they occur six times more frequently in men than in women. This is probably related to the higher incidence of androgenetic alopecia and a higher cumulative and intermittent ultraviolet damage on the scalp. Histologically, SM is a heterogenous group, including lentiginous melanoma (LM), desmoplastic melanoma, superficial spreading and nodular melanoma. Thin melanomas tend to display an atypical network or pseudo-network and regression in dermoscopy. Blue-white veil, irregular pigmented blotches and an unspecific pattern are most commonly detected in thick lesions. On reflectance confocal microscopy (RCM), the most frequent pattern is irregular meshwork, but also ringed and disarranged pattern have been described. Differential diagnosis includes benign solar lentigo, actinic keratoses, lichen planus like keratosis, melanocytic nevi and blue nevi. All suspicious lesions should be biopsied; therefore, an excisional biopsy with 2 mm margins is usually the best option. The management of SM is the same as for melanoma on other body sites. However, sentinel node biopsy tends to be more challenging, as well as achieving adequate excision margins of the primary tumor. In this review, we summarize clinical, pathologic, dermoscopic and RCM features of SM, and focus on its epidemiology, risk factors and best management options.Keywords: scalp, melanoma, dermoscopy, reflectance confocal microscopy